Faktor-Faktor yang Mempengaruhi Kualitas Hidup Anak Berkebutuhan Khusus Cerebral Palsy di Surakarta: Faktor-Faktor yang Mempengaruhi Kualitas Hidup Anak Berkebutuhan Khusus Cerebral Palsy di Surakarta - Sukadarwanto; Yulianto Wahyono; Nitaya Putri Nur Hidayati (Jurnal Nasional Fisioterapi, 2026)
Background : Cerebral Palsy (CP) is the leading cause of physical disability in children, with multidimensional impacts on Quality of Life (QoL). This study explores factors influencing QoL from the perspectives of children and parents in Surakarta. Objectives : (1) To describe the QoL of children with CP aged 8-12 years based on perceptions from children and parents; (2) To analyze related factors. Methods : This is a descriptive analytic study with a cross-sectional design, involving a sample of 89 pairs of children with CP (aged 8-12 years, GMFCS Level I-V) and their parents/caregivers residing in Surakarta, selected using consecutive sampling. Independent variables: child characteristics (age, gender, GMFCS Level, presence of seizures and pain) and family characteristics (parental education, occupation, family income). Dependent variable: QoL scores measured using two versions of the Cerebral Palsy Quality of Life Questionnaire for Children (CP QOL-Child): child self-report for communicative children or parent proxy-report. Data analysis: univariate (descriptive), bivariate (Spearman, and multivariate multiple linear regression. Results : The majority of subjects had moderate motor impairment (GMFCS Level III). QoL scores from parent reports were lower in the domains of social participation and emotional well-being. Significant bivariate factors: GMFCS Level (p=0.001), chronic pain (p=0.012), and family income (p=0.018). Multivariate analysis: all three factors as significant predictors, with GMFCS Level as the dominant one (β=-0.407; p<0.001). Conclusion : QoL of children with CP in Surakarta is influenced by multiple factors, with motor severity as the primary determinant. Comprehensive pain management and socio-economic support are crucial. Clinical implications: integrative family-centered care approaches.